Exploring the Use of the Suzuki Coupling Reaction in the Synthesis of 4′-Alkyl-2′-hydroxyacetophenones - Pouget, Christelle; Trouillas, Patrick; Gueye, Rokhaya; Champavier, Yves; Laurent, Aurélie; Duroux, Jean-Luc; Sol, Vincent; Fagnere, Catherine (Synlett, 2014)
A series of 4′-alkyl-2′-hydroxyacetophenones were prepared by Suzuki cross-coupling reactions of 4′-bromo-2′-hydroxyacetophenone. In these reactions, alkyl(trifluoro)borates were found to be better reactants than alkylboronic acids. 4′-Alkyl-2′-hydroxyacetophenones are key intermediates for the further synthesis of lipoflavonoids that are more readily incorporated into lipid bilayer membranes than flavonoids and should, therefore, have superior biological effects through increased bioavailability.
Keywords: alkylation; cross-coupling; catalysis; palladium; ketones